The Influence of Product Quality and Service Quality on Purchasing Decisions at Richeese Factory Restaurants in Makassar City - Fatmawati A Rahman; Masmarulan R (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2023)
The research was conducted with the intention of evaluating how product quality and service influence purchasing decisions at the Richeese Factory branch in Makassar city. Product quality and service are identified as factors that have the potential to influence how consumers make purchasing decisions. Quantitative methods were used in this study, and questionnaires as a medium to collect data from Richeese Factory consumers in Makassar. The results of the analysis suggest that there is a positive and significant effect of product quality and service quality on purchasing decisions. The product quality for the regression coefficient is 0.345, which indicates that each increase in product quality will increase purchasing decisions by 0.345 points. In addition, the service quality for the regression coefficient is 0.497, which means that if each increase of 1 point in service quality will increase purchasing decisions by 0.497 points. This confirms that both product quality and service quality have a positive and important effect on the decision to purchase consumer products or services. This is in line with theory and previous research which emphasizes the importance of maintaining product quality and service quality.